Investigation of The Dimensions of Religiosity Nolam Siti Saripah in Harapan Harapan Insyaf Manuscript - Roziah; S, Ermawati; S, Hermaliza; Nurhidayah; Puspita, Alvi; Elia, Fitra (Literasi Nusantara, 2025)
This investigation of the religious value of nolam manuscripts handwritten in jawi script in the almost extinct oral tradition of the Kampar people aims to bring back the teaching instructions to the public. The analyzed nolam entitled Siti Saripah was found in the Harapan-Harapan Insyaf Abu Yazid Abdullah manuscript in Jumadil Akhir 1370H - 1955M. The main focus analyzed from this nolam manuscript is the five dimensions of religiosity according to Strack and Glock. They are Religious Belief Religious practice, Religious Feeling, Religious Knowledge, and Religious Effect. The approach used in this study is a descriptive qualitative approach with three data collection techniques including script transfer from jawi writing into Indonesian, then reading while marking and recording good stanzas that contain dimensions of religiosity. The results showed that 58 out of 129 Siti Saripah's nolam stanzas contain religious values. The percentage of religiosity from the belief dimension is 50%, the worship dimension is 18.97%, the practice dimension (recommendation to do noble deeds) is 25.86%, and 5.17% for the dimension of prohibition to do despicable deeds. It can be concluded that the belief dimension is the dimension that occurs most often in life, because both have a lot to do with all daily activities, thus leaving a track record in the memory of the objectors.